The Impact of Internal Auditor's Creative Abilities on the Quality of ESG Sustainability Reports in Industrial Companies A Field Study on a Sample of Companies in the Cement Industry Sector in Sudan (Sebha University Conference Proceedings, 2024)
This study aimed to identify the impact of the internal auditor's creative abilities, including personal capabilities, idea generation, and intellectual flexibility, on the quality of ESG sustainability reports in industrial companies. The study employed a descriptive-analytical method and included the staff of internal audit departments in cement companies (Salam, Takamul, Nile, EL-Shemal,  Barbar) in Sudan, totaling 80 individuals. The sample was selected using a comprehensive survey method, and a questionnaire was used as the data collection tool. The study concluded that the dimensions of the internal auditor's creative abilities enjoy a high level of approval among respondents, with significant attention to the quality of ESG sustainability reports, achieving a relative importance of 78.85%. Additionally, there was a statistically significant impact of the internal auditor's creative abilities on the quality of ESG sustainability reports in Sudanese companies. The study recommended enhancing training programs focusing on developing the intellectual flexibility of internal auditors and improving their personal capabilities to enhance overall performance. It also suggested improving the timing of ESG report issuance, ensuring they contain relevant and unbiased information with a high degree of clarity to boost user confidence and comprehension. Furthermore, the study emphasized the need to enhance and develop the creative abilities of internal auditors through advanced training programs and workshops focusing on creativity and innovation, contributing to the improvement of ESG report quality.